Anatomical and histological study of the thymus gland in native rabbits (Oryctolagus cuniculus) - Iman Musa Khaleel (Al-Qadisiyah Journal of Veterinary Medicine Sciences, 2018)
The aim of this study is to add the available information of the anatomy and documenting the normal microscopic features of the thymus gland in rabbits, for this reason, ten rabbits from the local breed aged between (5-7) weeks breeding in animal house. After anesthetic the healthy animals intramuscularly in the thigh, the thoracic cavity opening by surgical scissor, to entering the thymus to study it anatomically and collected the specimen for histological study. The animals divided into two groups: the first group for the anatomical a study and the second group for histological study, the results appear that thymus of rabbit occupy most the thoracic inlet, pyramid in shape, white to yellowish in color, located rostral of the mediastinum area which covered the large vessel of the heart and aortic arch. The thymus is lobulated organ invested by capsule contain from loose connective tissue each the lobe consist of two different area, the peripheral area was deep stain called cortex and the inner pale area called the medulla, which contains different cells of lymphocyte and epithelial cells which noted arranged in concentric layers forming Hassall ś corpuscles.